Digital Serial Images in Elementary Story Writing: Gambar Serial Digital dalam Penulisan Cerita Dasar - Madinah, Wardhatul; ZULIKHATIN NUROH, ERMAWATI (Indonesian Journal of Education Methods Development, 2025)
General background: Writing skills are fundamental in elementary education, yet many students struggle to develop structured and meaningful narratives. Specific background: Traditional teaching methods often fail to stimulate creativity and engagement, requiring innovative media to support students’ learning processes. Knowledge gap: Although visual media has been studied, limited research addresses the integration of digital serial images as a systematic tool in elementary story writing. Aim: This study investigates the role of digital serial image media in improving story writing skills among second-grade elementary students. Results: Using a pre-experimental one group pretest-posttest design with 20 participants, the study revealed significant improvement in students’ writing scores, with statistical analysis showing p = 0.00 (<0.05). Novelty: Unlike conventional visual aids, digital serial image media provides a sequential and contextual framework that guides students in organizing ideas coherently. Implications: Findings suggest that integrating digital serial images can strengthen students’ creative expression and narrative construction, offering practical insights for teachers to enrich language learning in elementary schools. Highlights: Digital serial images foster structured narrative writing. Significant improvement shown in posttest results. Practical implications for language learning in elementary schools. Keywords: Digital Serial Images; Story Writing; Elementary Students; Learning Media; Language Education